2010
DOI: 10.1016/j.neuroscience.2010.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Activation of α1 and α2 noradrenergic receptors exert opposing effects on excitability of main olfactory bulb granule cells

Abstract: The mammalian main olfactory bulb (MOB) receives a dense noradrenergic innervation from the pontine nucleus locus coeruleus that is important for neonatal odor preference learning and odor processing in mature animals. Modulation of GABAergic granule cells (GCs) is thought to play a key role in the net functional impact of norepinephrine (NE) release in the MOB, yet there are few direct studies of the influence of NE on these cells. In the present study we investigated noradrenergic modulation of GC excitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
63
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 55 publications
14
63
1
Order By: Relevance
“…Specifically, low concentrations of NE (0.1-1.0 M) or ␣2-receptor agonists hyperpolarized and inhibited granule cell spontaneous or evoked spike discharge (Nai et al 2010). By contrast, 10 M NE or ␣1-receptor agonists depolarized and increased granule cell discharge.…”
Section: Noradrenergic Modulation Of Bulbar Processing: Electrophysiomentioning
confidence: 91%
See 1 more Smart Citation
“…Specifically, low concentrations of NE (0.1-1.0 M) or ␣2-receptor agonists hyperpolarized and inhibited granule cell spontaneous or evoked spike discharge (Nai et al 2010). By contrast, 10 M NE or ␣1-receptor agonists depolarized and increased granule cell discharge.…”
Section: Noradrenergic Modulation Of Bulbar Processing: Electrophysiomentioning
confidence: 91%
“…Modulatory inputs on mitral and granule cells can potentially affect the dynamics of neural activity as well as spike timing and degrees of synchronization. Levels of synchronization among bulbar outputs have been proposed to contribute to odor processing and learning experimentally (Beshel et al 2007;Brea et al 2009;Kay et al 2009;Nusser et al 2001). Modulatory inputs to granule and mitral cells can potentially regulate oscillatory dynamics of olfactory bulb processing and hence change the processing of odors, as proposed early on by Freeman and colleagues (Di Prisco and Freeman 1985;Gray et al 1986) and shown recently in slices of young rats by Schoppa and colleagues (Gire and Schoppa 2008;Pandipati et al 2010).…”
Section: Olfactory Bulb Network and Processingmentioning
confidence: 96%
“…In a recent publication Nai et al (2010) reported that NA can either increases or decrease the excitability of adult granule cell depending on the applied concentration and the noradrenergic receptors subtype activated. Such effects were mediated by variation in the membrane resistance (R m ) through a modification of potassium conductance.…”
Section: Blocking Neurogenesis Prevents Na-induced Improvement In Olfmentioning
confidence: 99%
“…The evidence that clonidine reduces granule cell activity (Nai et al 2010;Pandipati et al 2010) predicts elevated mitral cell excitation during odor paired with clonidine. We performed pCREB immunohistochemistry as an index of mitral cell activation and to assess the role of CREB in the clonidine model.…”
mentioning
confidence: 99%
“…Recently, studies of a 2 -adrenoceptor activation in the olfactory bulb in vitro have revealed receptor effects that could promote odor learning (Nai et al 2010;Pandipati et al 2010). In particular, the a 2 -adrenoceptor agonist, clonidine, has been shown to decrease granule cell excitability (Nai et al 2010), releasing the odor-encoding mitral cells from tonic inhibition, and to promote olfactory bulb synchrony at g EEG frequencies (Pandipati et al 2010).…”
mentioning
confidence: 99%